Kualitas Kehidupan Religiusitas Kristen di Tengah Masyarakat Pluralitas Berdasarkan Kajian Teologis Matius 22:34-40 - Kordin Sagala; Ayub Rusmanto (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
This paper analyzes the quality of Christian religious life in a pluralistic society based on the theological study of Matthew 22:34-40. Of course, previous researchers have examined the passage Matthew 22:34-40 with different studies. Thus, this article focuses on how the law of Christ's love remains relevant in a pluralistic world society. And the method used in this research uses a qualitative method which is built with a literature study approach and a Biblical hermeneutic approach. In realizing the quality of Christian religious life in a pluralistic society based on Matthew 22:34-40, the author finds that every Christian must be aware of and understand his calling in life in the midst of this heterogeneous world. The law of love based on Matthew 22: 34-40 is never out of date and remains relevant in every age, wherever and whenever. Loving God means at the same time loving fellow human beings. Ignoring the one thing between love for God and love for fellow human beings is the same as ignoring both. Love for God and love for fellow human beings are two laws that cannot be separated from one another. And the object for the application of God's law of love is the world and its pluralistic society. The quality of Christian religiosity can be seen from the way of life that loves God and also loves fellow human beings based on the law of love of Christ.